Soil mycobiome in sustainable agriculture - Frąc, Magdalena; Hannula, Emilia Silja; Bełka, Marta; Salles, Joana Falcao; Jedryczka, Malgorzata (Frontiers in Microbiology, 2022)
Recent advances in high-throughput sequencing combined with bioinformatic tools enable detailed studies of the soil microbiome. Its composition is important in sustainable crop production, in agriculture, horticulture and forestry. In contrast to vast studies of bacteria inhabiting soils, the amount of research on fungi composition is uncommon. This contrasts with the crucial role of fungi in the circuit of matter and energy on Earth. Fungi constitute a great part of a plant pathobiome, but many of them are also indispensable for plant health. This includes mycorrhizal fungi as well as superparasites of pathogens and some generalists which stabilize the soil mycobiome and play a key role in the cycle of elements. Fungal mycelium is stretched below ground like blood vessels in the human body and transfers water and nutrients to and out of the plants. Moreover, fungi have a unique ability to uptake high amounts of major and rare elements from the environment, which can be used in soil bioremediation. The studies of the composition of soil mycobiome require modern tools, and the overall results are useful in sustainable/regenerative agriculture.